Effects of Vernonia amygdalina and Azadirachta indica Extracts on Postharvest Weight Loss and Shelf Life of Tomato (Solanum lycopersicum L.) Cultivars - Folasade Ade-Ogunnowo; Oluseyi Adejoye (Salaga Journal, 2026)
Postharvest weight loss is a major constraint on tomato (Solanum lycopersicum L.) shelf life in tropical environments. This study evaluated ethanol and aqueous leaf extracts of Vernonia amygdalina (bitter leaf) and Azadirachta indica (neem) for their effects on weight retention and storage kinetics of San Marzano and Royal tomato cultivars over 20 days at ambient conditions (28 ± 2°C). Treatments comprised ethanol extracts (50–200 g/500 mL), aqueous hot and cold extracts (50 g/500 mL), and a distilled water control in a completely randomised design. Physiological loss in weight (PLW) differed significantly among treatments (p < 0.05). The 100 g/500 mL ethanol extract of bitter leaf gave the lowest PLW and highest weight retention, in Royal (37.3%) followed by San Marzano (41.9%). Hot aqueous extracts showed moderate efficacy (46.2–50.3% PLW), cold aqueous extracts were least effective (70.7–77.3%), and excess ethanol (150–200 g/500 mL) accelerated deterioration (81.6–86.9% PLW), indicating phytotoxicity. Weight loss followed an exponential decay pattern (R² = 0.91–0.98), with lower decay constants in optimised treatments (k ≈ 0.063–0.069 day⁻¹). Royal consistently showed greater postharvest stability than San Marzano. These findings indicate that a 100 g/500 mL V. amygdalina ethanol formulation offers an accessible, low-cost postharvest coating that can extend tomato shelf life and reduce reliance on synthetic fungicides for smallholder farmers in tropical regions.